Análisis al sistema de costos de producción y su incidencia en la rentabilidad de la pasteurizadora “Tanilact”, durante el primer semestre del 2011 - Cando Toapanta, Mercedes Janeth (2015)
The research is focused on "ANALYSIS SYSTEM OF PRODUCTION COSTS AND ITS IMPACT ON PROFITABILITY OF PASTEURIZER “TANILACT”, through this application can get the optimization of production costs and spends where we will give to know the aggregate value of the product, it is creating an image related to the quality and innovation of the enterprise what is analyzed; it is considered medium for its daily production, that is, which seeks the technification of its products into the productive process, this have as aim to achieve a significant increase to the demand of their products, in order to remain in the competitive dairy market and thereby, satisfy the customer, this has been the need of doing an analysis to the production costs, the same that will allow to determine with clarity and accuracy the unit costs in the productive process, through the optimization of raw material, labor and manufacturing overhead costs, which will allow the enterprise improve its productive activity, the control and efficient use of resources, so, this way could get higher profitability being favorable and beneficial for the pasteurizer